Treatment of high salinity sulfanilic acid wastewater by bipolar membrane electrodialysis - Sun, Yue; Wang, Yuanyuan; Peng, Zheng; Liu, Yan (Separation and purification technology, 2022)
•BMED was applied for desalination of sulfanilic acid wastewater for the first time.•Operating conditions were investigated to obtain the optimum parameters.•Mechanism of sulfanilic acid migration to adjacent compartments was discussed.•Process cost of BMED applied for treating sulfanilic acid wastewater was estimated. Sulfanilic acid (SA) is an important organic compound with numerous applications in industrial production, while the organic wastewater with high salinity is inevitably generated. In this work, desalination strategy of hypersaline SA wastewater was proposed by using bipolar membrane electrodialysis (BMED), which can realize the separation of SA and NaCl in wastewater and the conversion of NaCl into HCl and NaOH simultaneously. The influences of current density, initial concentrations of acid, base, SA and salt were investigated. The results showed that current efficiency decreased and energy consumption increased with an increase in current density. Higher initial concentrations of acid and base were favor to reduce energy consumption but current efficiency was low. At the current density of 40 mA/cm2, the initial acid and base concentrations of 0.10 mol/L, the highest concentrations of HCl and NaOH with initial salt concentration in the simulated feed solution of 80 g/L NaCl was 1.17 mol/L and 1.18 mol/L, respectively. Moreover, the total process cost of BMED process was estimated at $1.68/kg HCl and $1.52/kg NaOH respectively under the optimal experimental conditions. These findings confirmed that BMED may be an alternative and cost-effective strategy for treating high salinity SA wastewater.